Interactions of biologically active molecules, cofactors, and drugs with model membranes - Van Cleave, Cameron, author; Crans, Debbie C., advisor; Van Orden, Alan K., committee member; Levinger, Nancy E., committee member; Roess, Deborah A., committee member (Colorado State University. Libraries, 2021)
The cell membrane is important for the structure, function, and overall homeostasis of the cell. It consists mainly of phospholipids which have different physicochemical and material properties. As such, molecular interactions between the membrane's components and its environment are of importance. This manuscript explores the interactions of different classes of molecules with model membrane systems to gain a fundamental understanding. Chapter 1 provides background on the cell membrane and current models as well as an introduction to lipoquinones and small molecule drugs. Chapter 2 discusses the interactions of menadione and menadiol with Langmuir monolayers and reverse micelles. Menadiol and menadione are representative of the headgroup of menaquinones, a class of electron transporter, hence they are redox active. We hypothesized that the respective locations of menadione and menadiol within the membrane would vary due to their different physicochemical properties. We used Langmuir monolayers and NMR of reverse micelles to explore the location and association of menadione and menadiol with model membrane interfaces. Chapter 3 investigates the location, association, and conformation of truncated menaquinones with Langmuir monolayers and simulated bilayers. Previous work found that truncated menaquinones fold at the interface of a reverse micelle, so we hypothesized that subtle differences in folding would cause variations in location and association with phospholipids. We used a combination of Langmuir monolayers and molecular dynamics simulations to probe location, association, and conformation of truncated menaquinone homologues, MK-1 through MK-4, in a phospholipid membrane. Chapter 4 explores the pH-dependent effects of two anti-tubercule molecules at the membrane interface. Recent studies have suggested that pyrazinoic acid behaves as a protonophore and we further explored this suggestion while simultaneously exploring physicochemical properties of pyrazinoic acid and pyrazinamide. This chapter utilized a combination of Langmuir monolayers, NMR, and fluorescence leakage studies to characterize the molecular interactions of pyrazinoic acid with model membranes so that POA could be compared to a previous study with benzoic acid, a known protonophore.
Keywords: cell membrane; interactions; molecules; phospholipids